Handbook-INC: Inclusive Multiliteracy Development for All - Nap, Laura; Abdul Hussain, Doaa; Mc Tiernan, Kathleen; Carson, Lorna (Read With MEE, 2026)
This handbook, developed by the Read With MEE Project, is a practical, research-informed guide designed to support the language and literacy development of young children. Written in plain, accessible language, it brings together the latest insights from literacy, linguistic diversity, and multilingualism research, making complex findings easy to understand and apply. This handbook is perfect for early childhood educators, parents, caregivers, and anyone interested in the area of Early Childhood Education and Care. It provides clear guidance on best practices for fostering multiliteracy, helping children unlock reading as a superpower—building confidence, curiosity, and the ability to connect with multiple languages and cultures. Grounded in research, it equips readers with tools and strategies that can be used every day, both in classrooms and at home.
Read With MEE: Read with Multilingual Early Education
PUBLISHED
Trinity College Dublin, School of Linguistic, Speech and Communication Sciences
Read with MEE (Read with Multilingual Early Education) is a three year Erasmus+ KA2 partnership project (2023–2026) co-funded by the European Union that aims to advance early literacy development for young multilingual children, especially those aged 2–6 years who come from diverse linguistic backgrounds, including national, regional, migrant, and refugee minority language communities. The project addresses the fact that multilingual children often face unequal educational opportunities compared with monolingual peers, by promoting reading approaches that value and include all of a child’s languages, rather than treating languages separately. It emphasises interactive and engaging book reading in multilingual contexts, encouraging positive attitudes towards linguistic diversity and support for home languages. Read with MEE brings together partners from the Netherlands, Belgium, Ireland, and Spain and collaborates with professionals and experts to ensure its outputs are grounded in the latest research on multilingual and early literacy development. Read with MEE seeks to strengthen knowledge, skills, and classroom/home practices that support inclusive and multilingual early literacy development across Europe.
Keywords: Education and minority language; Minority language education and maintenance; Multilingualism